Design of a Compact Wideband Balun Bandpass Filter with High Selectivity - Ma, Hui; Lu, Jiayuan; Li, Yuran; Liu, Lin; Wang, Jianpeng (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A new design method for compact wideband balun bandpass filter (BPF) with high selectivity is proposed in this paper. To achieve wide operation bandwidth, the first three resonant modes, i.e., one odd mode and two even modes, of a folded stepped-impedance multi-mode resonator are utilized and arranged inside the passband. Then, to realize good balance-to-unbalance performance, a microtrip to coplanar stripline transition structure is introduced in the design. Finally, a balun BPF characterized with both wide bandwidth and high selectivity has been eventually achieved through proper coupling topology. Besides, to further demonstrate the validity of our design concept, a practical microstrip wideband balun BPF with the fractional bandwidth (FBW) of 66% and two respective transmission zeros located at 1.4 GHz and 4.2 GHz is designed, fabricated, and measured. As expected, both the simulated and measured results exhibit good filtering and balun performance.